Prospek dan Hambatan Industri Tekstil dan Produk Tekstil (TPT) Nasional - Supomo Supomo (Majalah Ilmiah Ekonomi Komputer, 2007)
It is the fact that textile industry and textile products are labour intensive. These two sectors become the second rank in contributing foreign exchange petroleum and LNG (Liquid Natural Gas) due to export to the United States and other European Countries. While the sectors used to be the best ones in industry, now they are facing two major problems. The first is international competition against Cina and India. The second problems are investment condition, high cost economy and banking. The government is summoned to revive the dying sectors through clean and concrete programs which in return will reduce the rate of unemployment keywords : power supply, competitiveness, investment environment, politics willingness